Factors affecting the profitability of smallholder broiler production in Mutare district, Manicaland Province, Zimbabwe: A quantile regression approach - Precious T. Phiri; Freddy Ruzhani; Faustino Madzokere; Pamela Madududu (Cogent Economics & Finance, 2023)
Small-scale broiler farming has become one of the fastest-growing sub-sectors in Zimbabwe. However, the profitability levels of these small ventures have been questioned due to the rising production costs owing to the highly inflationary macroeconomic environment. Using a sample of 110 small-scale broiler producers selected using the exponential non-discriminative snowballing sampling method, the paper analysed the factors affecting these farmers' profitability. Gross margin analysis and quantile regression were used to analyse the data. We found that, although feed costs constituted 56.8% of the total variable costs, small-scale broiler production is a profitable venture in the area with a mean gross margin of US 65.25 per batch of 100 broilers and a return per dollar variable costs invested of 1.15. Training on broiler production, farming experience, level of education, access to extension services, access to credit and household size significantly determine the profitability of the broiler enterprise at various quantiles, with only training affecting profitability at all three quantiles. All these factors are essential contributing factors to the profitability or lack thereof of small-scale broiler production in Mutare district. We recommend that training programs on effective broiler production be offered to small-scale farmers in the Mutare district. The government and non-governmental organisations should also develop small loan packages that can assist the farmers in improving their production levels and profits. Government extension workers should be more visible and accessible to the farmers in peri-urban areas to positively influence their profitability levels.
Keywords: 330; broiler production; gross margin analysis; profitability; quantile regression; Zimbabwe